Letter from Campbell Morfit to Margaret M. Booth, December 10, 1888 - Morfit, Campbell (1888)
Campbell Morfit (1820-1897), a distinguished chemist from the United States and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Margaret M. Booth née Cardeza to mourn her late husband's death.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Martinez Cardeza, Margaret